ETANOLÜN UYGULANMA DOZU VE SÜRESİNE BAĞLI OLARAK ALKOLİK GEBELERDE İMMÜN SİSTEM DEĞİŞİMLERİ - AKYOL, Sibel; TUNALI, Halil (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Maternal immunosuppression and immunotolerance are required during a successful pregnancy. Differential regulation of the immune system by the maternal immune system enables this interaction during pregnancy. Effect of teratogenic substances used during fetal development on the maternal immune status is not fully understood. Our purpose was to study the role of alcohol on the maternal immune system following a variety of doses and administration routes. Wistar albino rats (10-12 weeks of age) were used in this study. Six experimental groups (n=10 each) consisted of controls (C), control pregnant (CG); those who received 17.5% ethanol by diet (E), and their pregnant counterparts (EG), and the 30% gavage ethanol group (GE) and pregnant rats treated similarly (GEG). Group administered ethanol by diet was treated for 4 months (8.75 g/kg/day); and gavage was treated for 2 months (6 g/kg/day). Subsequently these rats were impregnated, and ethanol treatments were continued. Lymphocytes were analyzed by flow cytometry for CD3, CD4, CD8 and CD19. IL-1 and IL-2 levels were determined by ELISA. Results.- Ethanol treated group demonstrated significant increase in CD4, CD3 and IL-1 compared to the control group. Same group demonstrated decrease in CD8, CD19 and IL-2. In the gavage group there was no change in CD4, CD3, CD19 and IL-1, however IL-2 and CD8 were decreased compared to controls. In the pregnant groups there was decrease in CD4, CD8, CD19 and IL-2 in the EG group compared to control pregnant rats, and CD3 and IL-1 were increased. Comparison of the GEG to CG showed that there was no change in CD4 and CD3, decrease in CD8, CD19 and IL-2, and increase in IL-1. When experimental groups were compared to controls, there was decrease in CD4 (18%), CD3 (19%), IL-2 (24%) in the control pregnant group compared to controls. There was no change in CD8 and CD19, however IL-1 (28%) was increased. When ethanol treated pregnant group was compared to ethanol group, significant increases in CD4 (%46), CD8 (%20), CD3 (%22), CD19 (%31) and IL-1 (%34) were seen. In the pregnant gavage group decrease in CD4 (%24), CD8 (%13), CD3 (%24), CD19 (%23), and IL-2 (%15), and %29 increase in IL-1 was demonstrated compared to non-pregnant gavage group. Most significant changes were observed in the long-term ethanol treated group. Conclusion.- Our results demonstrate that ethanol administration resulted in variable amount of immunosuppression in pregnant rats depending on the duration and method of administration.